Advanced therapeutic strategy for managing surgical site infections with natural nanoemulsion-antimicrobial combination - Alshehri, Fatma; Alharbi, Nada K.; Zaid, AbdelNaser; Eltrawy, Amira H.; Fawzy, Shereen; Gabr, Attia M.; Zaitone, Sawsan A.; Alhomrani, Majid; Alamri, Abdulhakeem S.; Mosbah, Rasha A.; Elshimy, Rana; Mansour, Abdallah Tageldein; et al. (Frontiers in Pharmacology, 2025)
IntroductionSurgical site infections (SSIs) are a significant cause of morbidity and mortality, often complicated by multidrug-resistant (MDR) pathogens and biofilm formation. This study evaluates the potential of a natural nanoemulsion containing chitosan, lavender, and curcumin, in combination with antimicrobial drugs, for treating SSIs.MethodsA comprehensive approach combining phenotypic and genotypic analyses, along with in vitro and in vivo studies, was used to assess the efficacy and safety of the combination therapy.ResultsThe most common SSI pathogens identified were Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii, with 50% exhibiting MDR, biofilm formation, and multiple virulence factors. Chitosan nanoemulsion showed the lowest minimum inhibitory concentration (MIC) (300–500 μg/mL), although it exceeded the cytotoxicity safety threshold (200 μg/mL). However, it significantly enhanced the antimicrobial activity of amikacin, resensitizing resistant strains at safe concentrations. The combination therapy of amikacin and chitosan nanoemulsion demonstrated superior efficacy in reducing bacterial loads in both Gram-negative and Gram-positive infections. In vivo studies showed near-complete bacterial clearance by day 12. Histopathological analysis revealed enhanced wound healing, reduced inflammation, and restored tissue function. The combination of amikacin and chitosan nanoemulsion presents a promising therapeutic strategy for managing SSIs caused by MDR pathogens, improving bacterial eradication and wound healing.ConclusionThis study highlights chitosan nanoemulsion as an adjuvant therapy to combat antimicrobial resistance, enhance antibiotic efficacy, and improve SSI treatment outcomes. Further clinical studies are needed to optimize its use in patient care.